Linking women-led community kitchens to school food programmes: Lessons learned from the Healthy Kitchens, Healthy Children intervention in Palestinian refugees in Lebanon - Ghattas, Hala; Choufani, Jowel; Jamaluddine, Zeina; Masterson, Amelia Reese; Sahyoun, Nadine R. (Cambridge University Press, 2020)
Decades of marginalization have led Palestinian refugees living in Lebanon to experience multigenerational poverty and food insecurity. The Healthy Kitchens, Healthy Children programme implemented and examined the impact of a two-pronged intervention that employed women through community kitchens to deliver a subsidized healthy daily school snack to elementary-school children in Palestinian refugee camps in Lebanon. We describe the rationale, study design, theorized impact pathways, and discuss lessons learned.The programme was quasi-experimental. We conducted formative and process evaluation of both components of the intervention to elucidate the pathways to programme impact.Palestinian refugee camps in Lebanon.Thirty-three women participated in the kitchens and provided subsidized snacks to 714 children.Snacks were healthy, traditional Palestinian recipes designed by women and a nutritionist. Participation fluctuated but eventually increased after modifying the meals to ensure acceptability by children. The main challenges to sustainability related to the need for subsidization of the meals and the lack of school policies around the regulation of sales of school food, which together led to fluctuations in programme participation.The study provides lessons learned on the potential of this model to improve the human capital of two generations of protracted refugees. The availability of schools as a constant market for these social enterprises offers an opportunity for sustainable livelihood generation and food security gains. Challenges to sustainability remain and could be addressed through social (subsidies to support the programme) and structural (policies to restrict unhealthy food sales) measures.